LACTIC ACID BACTERIA. II : INTERACTIONS AMONG STRAINS OF Lactobacillus AND Lactococcus ISOLATED FROM RAW MILKS OF WESTERN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2004)
This work deals with the bacterial interactions among 16 members of Lactococcus genera and 11 of Lactobacillus genera isolated from raw milk of cow or she-camel from Algeria and identified thanks to biochemical and physiological tests. We looked for inter-inhibitions on 729 intra-specific, inter-specific or inter-generic couples, the co-cultures being realized in a phosphate buffered (pH=7) or non-buffered solid medium, or with catalase. 16.5% cases of inhibition, 2.5% of which are cases of self-inhibition were observed among the couples of Lactobacillus, and 74% cases of inhibition, 4.7% of which correspond to cases of self-inhibition among Lactococcus couples. Among the couples Lactobacillus - Lactococcus we noticed 2.3% cases of inhibition when Lactobacillus strains were used as indicator strains and 82.5% when Lactococcus strains were used as indicators strains. Some cases of inhibition but not all cases can be attributed to acidity or hydrogen peroxide production. No inhibition due to temperate phage was detected.